2021
DOI: 10.3389/fimmu.2021.728021
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 mRNA Vaccines Elicit Different Responses in Immunologically Naïve and Pre-Immune Humans

Abstract: As the COVID-19 pandemic continues, the authorization of vaccines for emergency use has been crucial in slowing down the rate of infection and transmission of the SARS-CoV-2 virus that causes COVID-19. In order to investigate the longitudinal serological responses to SARS-CoV-2 natural infection and vaccination, a large-scale, multi-year serosurveillance program entitled SPARTA (SARS SeroPrevalence and Respiratory Tract Assessment) was initiated at 4 locations in the U.S. The serological assay presented here m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 47 publications
(55 reference statements)
4
23
0
Order By: Relevance
“…Consistent with other studies [34,36,37], our data confirm that subjects previously exposed to SARS-CoV-2 reach levels of protection against all tested variants after just one vaccine dose. Furthermore, we found a limited contribution, if any, of a second vaccine dose in pre-exposed individuals.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with other studies [34,36,37], our data confirm that subjects previously exposed to SARS-CoV-2 reach levels of protection against all tested variants after just one vaccine dose. Furthermore, we found a limited contribution, if any, of a second vaccine dose in pre-exposed individuals.…”
Section: Discussionsupporting
confidence: 92%
“…Other studies have also shown higher antibody responses in previously COVID-19 infected vs. naive individuals with both mRNA vaccines. 4,46,47 This is one of the first comparative COVID-19 vaccine immunologic durability studies; our results are consistent with results from two other studies (below). 3,35 A synopsis of the current literature shows many more studies reporting antibody and VE results for individual vaccines rather than comparative analyses.…”
Section: Discussionsupporting
confidence: 91%
“…Viral neutralization (VN) assays were performed in a Biosafety Level 3 (BSL-3) laboratory as previously described 10 . The USA-WA1/2020 SARS-CoV-2 strain (100 TCID50/50µl; NCBI accession number: PRJNA717311) was co-incubated with serially diluted serum samples for 1 hour at 37°C and then added to a monolayer of Vero E6 cells.…”
Section: Methodsmentioning
confidence: 99%
“…Anti-spike antibodies increase significantly following vaccination 10,11 . However, there is a significant drop in antibody levels within the first few months following vaccination [12][13][14] .…”
Section: Introductionmentioning
confidence: 99%